Frequency of Fungal Nasal Polyposis and its Associated Risk Factors - Muhammad Farooq Bhutta, Ashfaq Hussain, Salman Baig, Nadia Shahid, Nasima Iqbal, Urooj Zafar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the exactfrequency of fungal nasal polyposis and its associated risk factors. Methods: A descriptive cross-sectional study was conducted atENT department of Jinnah Postgraduate medical center (JPMC) from August 2020 to March 2021. The demographic data, detailed history and clinical examination of all the participants were noted. Specimen was sent in formalin solution for histopathological examination while another was sent in normal saline for culture and sensitivity of fungal infection. Gomorri Methylamine Silver stain and Periodic Acid Schiff stain were used to confirm the fungal hyphae. Statistical Package for the Social Sciences (SPSS) version 20 was used to analyze the data. p-value of less than 0.05 was considered as significant. Results: The mean age of the study participants was 30.29 ± 11.42. On histopathological findings, the Fungal nasal polyposis was reported among 43% of the individual while remaining were having allergic type of polyps. Out of 84 positive fungal cases, about 65.7% were aspergillus while remaining 34.3% of mucormycosis. About 17.2% of the cases were having BMI less than 30 and have no significant association. It had been found that majority of patients (43%) were farmers while about 39.9% were immunocompromised. Very few of them (22.6%) were having personal history of allergy. Conclusion: There is a high frequency of fungal nasal polyposis that is 43% in current setup. The disease is multifactorial and is predominant in farmers and in immunocompromised individuals.